Konstribusi Persepsi Kinestetik Terhadap Keberhasilan Smash dalam Permainan Bola Voli - Lalu Erpan Suryadi; Mahfuz Mahfuz; Muhammad Husni Tamim; Herman Afrian; Didik Daniyantara; Karno Dinata; Hariadi Hariadi; Deri Pratama Anugrah; Egiq Aditya Nanda Pratama; Fickri Hezizuari; Fitri Kartika; Husnan Majdi (Universitas Hamzanwadi, 2022)
The purpose of this study was to find out the relationship etween kinestetic perceptions and the succesful of smash in students’volleyball games. The result of this study were expected to provide an overview of the relationship between kinestetic perceptions and the succesful of the volleyball smash, so that it could be input for phisical education teacher and carrying out the learning. This study used descriptive research methode throught correlation aproach. The population used in this study was the total number of class VIII of SMP islam NW Ajan which consisted of 32 students. Meanwhile, the sample of this study was the entire population because it used a total sampling technique. Data collection in this study used test and measurements in sport and volleyball smash technique skill test. Bassed on the result of processing and analysis data, it could be concluded that the result of t-test found that the value of tcount was 5.477 and value of ttable at the degre off validity dk = n-2 and significance level of 5% was 2.042, which meant that kinestetic perceptions had a significant relationship on the succesfull of the smash in the volleyball game for VIII grade students of SMP islam NW ajan. The contribution of kinestetic perceptions to the succesfull smash in volleyball was 67.44% this showed that the better the student’s kinestetic perceptions ability, the better the succesful rate of their smash.